2008
DOI: 10.1016/j.neuropharm.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid CB1 cannabinoid receptor desensitization defines the time course of ERK1/2 MAP kinase signaling

Abstract: SummaryMolecular mechanisms regulating the development of physiological and behavioral tolerance to cannabinoids are not well understood. Two cellular correlates implicated in the development and maintenance of tolerance are CB 1 cannabinoid receptor internalization and uncoupling of receptor signal transduction. Both processes have been proposed as mediators of tolerance because of observations that chronic Δ 9 -tetrahydrocannabinol (THC) treatment causes both region-specific decreases in CB 1 receptors and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
153
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(167 citation statements)
references
References 38 publications
11
153
2
1
Order By: Relevance
“…As described in the introduction, the binding between β-arr2 and CB 1 R as well as a role for β-arrestins in the desensitization of CB 1 R have been demonstrated by former studies (Bakshi et al, 2007;Daigle et al, 2008aDaigle et al, , 2008bJin et al, 1999;Kouznetsova et al, 2002;Nguyen et al, 2012;Singh et al, 2011). Therefore, the role of β-arr2 in CB 1 R endocytosis may seem to be a logical consequence of its recruitment to the receptor.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As described in the introduction, the binding between β-arr2 and CB 1 R as well as a role for β-arrestins in the desensitization of CB 1 R have been demonstrated by former studies (Bakshi et al, 2007;Daigle et al, 2008aDaigle et al, , 2008bJin et al, 1999;Kouznetsova et al, 2002;Nguyen et al, 2012;Singh et al, 2011). Therefore, the role of β-arr2 in CB 1 R endocytosis may seem to be a logical consequence of its recruitment to the receptor.…”
Section: Discussionmentioning
confidence: 82%
“…Although the role of β-arrestin molecules in CB 1 R-mediated ERK activation has been suggested (Daigle et al, 2008a), the exact role of this process in CB 1 R-mediated ERK activation requires additional studies. It is very likely that the class A behavior of CB 1 R is associated with a characteristic distribution of MAPK activation, nevertheless, direct studies that address these questions are needed to confirm them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of AEA uptake by UCM707 abolished hyperkinesia in rodent models of HD and reduced spasticity in MS rats [178]. However, the elevation in AEA could produce psychotropic effects and tolerance upon CB 1 R activation [179], which has not been seen as a side effect of CBD [180]. Therefore, the binding of CBD to the AEA transporter will not provide a therapeutic effect in movement disorders.…”
Section: Cbd Transporter Targets In Movement Disordersmentioning
confidence: 99%
“…Although the inhibition of AEA uptake has produced anxiolytic responses in animal models, previous studies have shown that CB 1 R activation leads to psychotropic effects; this has never been observed following CBD treatment [279]. Furthermore, prolonged CB 1 R activation leads to tolerance, which has not been reported in CBD-treated animals [180]. Thus, it is unlikely that the AEA transporter is involved in the anxiolytic or antipsychotic effect of CBD.…”
Section: Cbd Transporter Targets In Psychosismentioning
confidence: 99%